Mainstreaming Women Farmers to Agricultural Extension Services in India: Perception of Extension Personnel - Uma Sah , Shantanu Kumar Dubey , S. K. Singh , Rajesh Kumar , Deepak Singh; Radha Krishna (Indian Journal of Extension Education, 2015)
The poor access of women farmers’ to agriculture extension services is an issue of concern with respect to the efficacy of the agriculture production situation in India. The present favorable policy environment enabling women farmers in accessing the extension services, the extension personnel plays the crucial role of translating these policies in achieving the desired results. In an attempt to comprehend empirically the extension personnel’s perception of the issue relating to mainstreaming women farmers to agricultural extension services in India, the study was conducted among 150 Extension Personnel (EP) who participated in capacity enhancement programmes during 2008-13 at ICAR- Indian Institute of Pulses Research (IIPR), Kanpur. Research variables included perception of EP on women farmers’ contribution to farming related activities, engagement of female workforce in respective district extension system, the issues related to involving women farmer in agricultural extension activities and the potential interventions to overcome the perceived issue. Finding revealed that in overall pooled data more than half (56%) of EP observed that woman farmers contributed 21-40 per cent to the overall agricultural activities, while 23 per cent of them perceived that women farmers contributed 41-60 per cent of the total labour to agriculture activities in their respective districts. In depth activity analysis showed that majority of the respondents reported that activities like weeding (87%), harvesting (85%), seed sowing (69%) and threshing (48.6%) were performed by women farmers. Regarding the strength of female extension staff in their districts, about 51 per cent of the EP revealed that the percentage of women extension staff was 0 to 5 per cent of the total existing staff strength. Majority of the EP also perceived that social taboos prevented women’s involvement in the extension activities (61%) besides their illiteracy (39 %). Nearly half (48 %) of EPwere not satisfied with the present level of women farmers’ access to agriculture extension services and about 83.3 per cent opined that women farmers need to be adequately involved in the agriculture extension activities. About 61 percent of them viewed that for better reach of extension services to women farmers, appointment of women extension staff needs priority attention. For mainstreaming women farmers in agricultural extension activities in India, majority of the EP suggested that designing specialized need based trainings for women farmers (50 %), approaching women in groups through SHGs or women’s club (20 %) and reserving thirty per cent seats for women extension staff (15%) in the department may ensure better access of agricultural extension services to women farmers in India.